Ocular emergencies. (December 2018) - Heng, L.Z.; Hamilton, Robin D.
Abstract: Ophthalmic emergencies vary widely in their nature, speed of onset and associated pathology. They can be life-threatening or sight-threatening. The medical practitioner needs to be able to identify when an ocular pathology requires intervention immediately or within 24 hours, or can be referred to outpatients. This chapter discusses the presentation, basic investigations and treatment that can save vision and, on occasions, life.